The suppression of rejection of Nippostrongylus brasiliensis in the rat by promethazine hydrochloride: The site of immunological impairment - Kelly, J. D. (1972)
Rats were treated parenterally with promethazine hydrochloride during a primary infection with Nippostrongylus brasiliensis. Survival of the parasites in the small intestine was prolonged and this suggested that promethazine inhibited rejection of the parasites. The site of immunological impairment in promethazine-treated animals was investigated by transfer of resistance to the parasite with immune lymphocytes. As previous studies have shown that the mechanism of rejection of helminths is diphasic, comprising specific lymphocyte—antigen reaction and involvement of myeloid cells and release of biogenic amines, it is conceptually possible that promethazine may act at either level. The functional activity of immune mesenteric lymph node cells, as assessed by their capacity to cause parasite rejection, was reduced by treatment of cell recipients with promethazine. In addition, lymphocytes from donors treated with promethazine during immunization were also markedly less effective than cells from untreated donors when transferred to syngeneic recipients. These results show that the in vivo effect of promethazine may be mediated at the specific lymphoid level as well as at the myeloid-amine level. Direct confirmation of this finding was obtained showing that serum from promethazine-treated rats seriously impaired the activity of immune lymphocytes in cellular transfer of resistance to N. brasiliensis. In this study immune lymphocytes were incubated at 37° for 1 hour with serum from promethazine-treated uninfected rats and then washed immediately before transfer to syngeneic recipients.